Bullying Prevention Strategies Among Vocational School Students: A Qualitative Study - Wardah, Ani (Kuras Institute, 2025)
This qualitative research investigates strategies for preventing bullying in Indonesian vocational high schools by conducting in-depth interviews with 12 teachers and 8 counsellors from 4 schools in Banjarmasin. The study identifies four main forms of bullying: verbal harassment, social exclusion, cyberbullying, and physical aggression, noting that underreporting is prevalent due to the normalisation of these behaviours and fear of retaliation. The findings indicate that although current interventions, such as counselling and awareness campaigns, show potential, their effectiveness is limited by three systemic challenges: (1) insufficient training for teachers in addressing cyberbullying, (2) inconsistent implementation of policies across different schools, and (3) a lack of parental involvement. To address these challenges, the research introduces a tripartite intervention model, a novel contribution to the field, integrating restorative justice practices, digital reporting systems, and community partnerships. This hybrid approach is particularly effective in vocational high school settings, where peer hierarchies and vocational pressures heighten the risk of bullying. Limitations of the study include its focus on a localised sample (n = 20) and the qualitative nature of the methodology, indicating the need for longitudinal research across Indonesia's diverse regions. These evidence-based strategies provide a new framework for policymakers aimed at reducing bullying-related disparities in vocational education.